(untitled) (Research, Society and Development, 2021)
Bacterial cellulose membrane (BCM) is a biomaterial synthesized by bacteria of the genus Gluconocetobacter hansenii with a higher degree of purity than plant cellulose. The commonly used raw material for manipulating bacterial cellulose is kombucha, a beverage consumed by a vast population around the world that promises health benefits. The beverage is composed of tea species Camellia sinenses and a carbon source, refined sucrose, and a starter culture of bacteria and yeast with 10% fermented tea (starter tea) to activate the fermentative process. The Kombucha’s bacterial cellulose membranes (KBCM) are formed over 7 to 10 days on the surface of the fermented product and have the appearance of a gelatinous membrane, this being the by-product of interest. In this work, the objective was to obtain the membrane composed of cellulose via Kombucha and purify it to obtain crystalline cellulose. The purification was performed with distilled water and 0.5M NaOH sodium hydroxide solution to remove residues from the fermentation, successfully removing sugars and bacteria. At the end of the experiments, a lighter film was obtained with coloration close to white, and comparative analyses were performed to verify the structural chemical composition, crystallinity, and morphology of the samples by techniques FTIR, DRX, and SEM, respectively. Then, once the biomaterial was purified, the range of applications expanded to several products to meet the biomedical area, sustainable packaging, and even the fashion industry.